2015
DOI: 10.4172/2157-7633.1000292
|View full text |Cite
|
Sign up to set email alerts
|

Differential Properties of Human ALP+ Periodontal Ligament Stem Cells vs Their ALP- Counterparts

Abstract: Characterizing subpopulations of stem cells is important to understand stem cell properties. Tissue-nonspecific alkaline phosphatase (ALP) is associated with mineral tissue forming cells as well as stem cells. Information regarding ALP subpopulation of human periodontal ligament stem cells (hPDLSCs) is limited. In the present study, we examined ALP+ and ALP− hPDLSC subpopulations, their surface markers STRO-1 and CD146, and the expression of stemness genes at various cell passages. We found that ALP+ subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The ALP + cells were collected from the column after adding the buffer and firmly pushing the plunger into the column. We found that using FACS or MACS yielded similar results (Yu et al 2015). In the present study, FACS was used for the data in Figs.…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…The ALP + cells were collected from the column after adding the buffer and firmly pushing the plunger into the column. We found that using FACS or MACS yielded similar results (Yu et al 2015). In the present study, FACS was used for the data in Figs.…”
Section: Methodsmentioning
confidence: 65%
“…The patient sample collection in this study was based on approved exempt protocols by the Institutional Review Board (IRB) of BU (#H-28882) and UTHSC (12-01937-XM); no patient consents were needed. The tissues were minced into 1 × 1 × 1 mm fragments, digested in collagenase/dispase and filtered through a 70-µm strainer to obtain single-cell suspensions as described previously (Huang et al 2010; Seo et al 2004; Yu et al 2015). Seeded cells were grown in α-minimum essential medium (α-MEM; Life Technologies/GIBCO BRL, Gaithersburg, MD, USA) supplemented with 10 % fetal bovine serum (FBS), 2 mM L-Glutamine, 100 µM L-ascorbic acid-2-phosphate and antibiotic/antimycotic agents as the regular growth medium (GM; pH 8.1); and maintained under 5 % CO2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of neurogenic genes was analyzed by real-time quantitative (q)PCR according to previous reports (Gauthier , et al , 2017, Yu , et al , 2015). Briefly, total RNA was extracted using an RNeasy Mini Kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Xu et al [ 9 ] demonstrated that BMSCs transplantation significantly enhanced new bone formation, but hyperlipidemia compromised homing efficiency of systematically transplanted BMSCs and inhibited bone regeneration. Alkaline phosphatase (ALP), engaged in bone matrix mineralization, and runt-related transcription factor 2 (Runx2), a master transcription factor of osteogenesis, were considered as early marker genes of osteogenesis [ 10 17 ].…”
Section: Introductionmentioning
confidence: 99%